Intraoperative pelvic brachytherapy for treatment of locally advanced or recurrent colorectal cancer - Turley, R. S. (2012)
BACKGROUND: The aim of this study was to evaluate the efficacy and morbidity of intraoperative radiation therapy (IORT) for advanced colorectal cancer. METHODS: All patients undergoing IORT for locallyadvanced rectal cancer from 2001-2009 were reviewed for cancer recurrence, survival and procedure-related morbidity. Cumulative event rates were estimated using the method of Kaplan and Meier. RESULTS: Twenty-nine patients with locally advanced (n=8) or recurrent (n=21) rectal cancers were treated with IORT and resection. Surgical interventions included low anterior resection, abdominoperineal resection, pelvic exenteration, and a variety of non-anatomic resections of pelvic recurrences. R(0) resections were achieved in 16 patients, while R(1) resections were achieved in 10, and margins were grossly positive in 3 patients. IORT was delivered to all patients over a median area of 48 (42-72) cm(2) at a median dose of 12 (12-15) Gy. Local and overall recurrence rates were 24% (locally advanced group) and 45% (recurrent group). Median disease-free and overall survival were 25 and 40 months respectively at a median follow-up of 26 (18-42) months. The short-term (≤30 days) complication rate was 45%. Eight patients developed local wound complications, 5 of which required operative intervention. Four patients developed intra-abdominal abscesses requiring drainage. Long-term (>30 days) complications were identified in 11 patients (38%) and included long-term wound complications (n=3), ureteral obstruction requiring stenting (n=1), neurogenic bladder (n=3), enteric fistulae (n=2), small bowel obstruction (n=1), and neuropathic pain (n=1). CONCLUSIONS: Intraoperative brachytherapy is a viable IORT option during pelvic surgery for locally advanced or recurrent colorectal cancer but is associated with high postoperative morbidity. Whether intraoperative brachytherapy can improve local recurrence rates for locally-advanced or recurrent colorectal cancer will require further prospective investigation.